A city hit by an earthquake: an HGIS approach to reconstructing the damage in Tiberias (Israel) in 1837. Issue 1 (2nd January 2017) - Zohar, Motti
ABSTRACT: On 1 January 1837 a devastating earthquake struck northern Ottoman Palestine, Lebanon and southern Syria, causing considerable damage in many localities. Tiberias, located on the western shores of the Sea of Galilee, suffered badly and many of its inhabitants were injured or perished. Yet, although the earthquake and the resulting damage were described in many contemporary sources, evaluation of the damage and its spatial distribution was never made before. In this study textual and visual sources were collected and compiled to evaluate the damage that resulted. An HGIS (historical GIS) approach was implemented to examine these sources, geo-code the damage and digitally reconstruct Tiberias at the time. The results were a contemporaneous map of Tiberias at the beginning of the nineteenth century and three-dimensional models of the city prior to and after the earthquake. The models enabled a 360º examination of the damage distribution in high resolution and evaluation of the overall impact of the earthquake. This study demonstrates the use of HGIS in the reconstruction of past urban cityscapes and the investigation of earthquake damage. It also suggests extending this methodology to other historical–geographical studies of past landscapes and to the examination of any kind of gradual or dramatic change.